Pengaruh Motivasi, Pengalaman, dan Self Efficacy Terhadap Kinerja Auditor - Nola Mahfuza; Dewi Zulvia (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to examine Motivation, Experience and Self Efficacy on Auditor Performance. Collecting research data using a questionnaire. The questionnaire was submitted to the Public Accountant Office in Padang City. This research is included in quantitative research. The sample is determined by purposive sampling technique. Data analysis uses multiple regression using SPSS 22 software. The results of this research show that Motivation has a positive effect on Auditor Performance, Experience has no effect on Auditor Performance and Self Efficacy has a positive effect on Auditor Performance.